PEMBANGKIT ENERGI PADA KNALPOT MOTOR 4 LANGKAH MENGGUNAKAN TERMOELEKTRIK GENERATOR - Arrassyid, Syadan; Anam, Khoirul; Towijaya, Towijaya (Surya Teknika : Jurnal Ilmiah Teknik Mesin, 2022)
Resources to produce energy is one of the increasing needs of society. So that there is an imbalance of load growth with the addition of power plants which will cause an energy deficit or an electrical energy crisis. There have been many studies on alternative energy power plants, one of which is the use of waste heat by using a thermoelectric generator. In this study, a thermoelectric power plant was tested by utilizing motorcycle exhaust heat for charging AAA batteries. When testing the output search, it was found that the highest current in a parallel circuit with 4 thermoelectrics is 104.4 mA and the highest voltage in a series circuit with 4 thermoelectrics is 0.83 V. Then, a AAA battery charging test is carried out using a 4 thermoelectric series circuit. From the results of the battery charging test, it was found that the battery voltage increased over the charging time period from the original 0.08 V to 1.05 V at the end of the charging time period. the current flowing in the circuit during the first 10 minutes is 48.2 mA, at the 20th minute it is 65.5 mA, at the 30th minute it reaches 91.2.Keywords: thermoelectric, energy generation, battery charging